Small worlds : maps and mapmaking - Young, Karen Romano; Fast, Ingo (New York : Scholastic Nonfiction, 2002)
Discusses different types of maps, how they are made, and tells about people who create them.
Includes bibliographical references (p. 120-121) and index.
School Library Journal.
Horn Book.
6.7
3-6
Keywords: Cartography -- Juvenile literature; Cartographers -- Biography -- Juvenile literature; Cartography; Maps; Cartographers; Maps; Cartographers; Cartography; Maps; Cartographers